A modular approach to volatile organic compound samplers for tethered balloon and drone platforms - M. Guagenti; D. Dexheimer; A. Ulinksi; P. Walter; J. H. Flynn III; S. Usenko (Atmospheric Measurement Techniques)
Situated at a land–sea interface, Houston, Texas, is a national hub for the petrochemical industry and has the second-fastest-growing metropolitan population in the United States. Addressing air quality in this region is uniquely challenging, due in part to its wide range of meteorological conditions (e.g., convection systems and temperature inversions) and continuum of volatile organic compound (VOC) and aerosol sources (e.g., anthropogenic and biogenic). As a result, Houston was chosen as the location for the Department of Energy's Atmospheric Radiation Measurement (ARM)-program-led Tracking Aerosol Convection ExpeRiment (TRACER), which investigated cloud and aerosol interactions in the deep convection over the area. Deployed as a key asset, ARM's tethered balloon system (TBS) was used to investigate questions related to the vertical distributions of aerosols and their formation, including their precursor species volatile organic compounds. Platforms like TBSs and uncrewed aerial vehicles (UAVs) can bridge the vertical gap between ground-based and crewed airplane measurement platforms to focus on near-surface characterization. However, there has been limited effort to modularize and integrate VOC samplers into instrument payloads on both aerial systems. In this study, lightweight and robust VOC samplers were designed and deployed on the TBS and a UAV to collect VOCs in flight. The modular design allowed for scalable adjustments to meet the unique platform requirements and enabled multiple flights per sampling day. Each sampler can autonomously collect VOCs on up to four sorbent tubes for subsequent thermal desorption–gas chromatography–mass spectrometry analysis. The low sampler mass (2.2 kg and 800 g, TBS and UAV, respectively) enables the combination of these VOC samplers with trace gas, aerosol, and meteorological sensors on aerial platforms. These profiles allow us to assess temporal changes in VOC magnitude and composition at multiple locations. Observations from TBS and UAV flights during TRACER are presented and future considerations for sampler design and deployments are discussed.